"Why would I go if the infant was healthy?": Factors Influencing Postnatal Care Utilization in Chiapas, Mexico. (July 2022) - Bancalari, Pilar; Alegre, Juan-Carlos; Mendez Alvarez, Montserrat; Sacks, Emma
Despite global efforts, postnatal care utilization remains low. There is almost no research on factors influencing postnatal care utilization in Latin America. Chiapas has one of the highest rates of maternal and neonatal mortality in Mexico. In 2014, we conducted 101 interviews with recently delivered women, male partners, traditional birth attendants (TBAs), and health staff, to assess factors influencing postnatal care utilization. Data underwent content analysis and thematic coding. Travel costs, postnatal seclusion practices, and a low perceived need for postnatal care were found to be disincentives to seek care. Providers ascribed low care adherence to cultural beliefs and low health literacy, while families indicated that their decision to seek facility care was mediated by the TBA's recognition of danger signs and perceived ability to manage complications. TBAs should be leveraged as gatekeepers, health literacy programs should emphasize the importance of primary care, and structural barriers to care should be reduced.